Narrowband ultraviolet B phototherapy is associated with a reduction in topical corticosteroid and clinical improvement in atopic dermatitis: a historical inception cohort study. (21st May 2021) - Choi, J. Y.; Owusu‐Ayim, M.; Dawe, R.; Ibbotson, S.; Fleming, C.; Foerster, J.
Summary: Background: Despite decades of use, the magnitude of efficacy of narrowband ultraviolet B (NB‐UVB) phototherapy for atopic dermatitis (AD) beyond industry‐sponsored trials remains unclear. Aim: To evaluate the clinical efficacy of NB‐UVB in AD under real‐world conditions. Methods: We conducted a historical inception cohort study using automated recording of dispensed drugs to provide an objective treatment outcome in a large population catchment of 420 000 people over 15 years. We analysed clinical treatment outcomes, recorded multicentre and prospectively over 15 years, of a large AD treatment cohort ( n  = 844), along with the drugs dispensed to this cohort. Results: The majority (70%) of patients with AD received significantly fewer topical corticosteroids (TCS) during the 12‐month window after finishing NB‐UVB compared with the 12‐month window before starting the treatment (median reduction from 37.5 to 19.7 g/month). The number of patients dispensed with oral corticosteroids and antihistamines also dropped significantly (from 20% to 10% and from 69% to 31%, respectively), while all AD‐unrelated drugs dispensed remained unchanged. Clinically, NB‐UVB treatment achieved a 'clear' or 'almost clear' status in 48.7% of patients, while 20.4% achieved 'moderate clearance'. Treatment outcomes scores were validated by a strong correlation with reduction in AD‐specific drug treatment. Conclusion: Our data confirm the significant efficacy of NB‐UVB for AD under conditions of routine care.